Microstructural effects on hardness and optical transparency of birefringent aluminosilicate nanoceramics. Issue 2 (10th January 2020) - Gaida, Nico A.; Nishiyama, Norimasa; Beermann, Oliver; Schürmann, Ulrich; Masuno, Atsunobu; Giehl, Christopher; Niwa, Ken; Hasegawa, Masashi; Bhat, Shrikant; Farla, Robert; Kienle, Lorenz
Abstract: Transparent nanoceramics, synthesized at extreme conditions of high pressure and temperature, are new classes of materials highly attractive for photonic applications, such as optical windows, which require additional increased hardness and toughness. In this study, mechanical properties of transparent polycrystalline nanoceramics consisting of triclinic Al2 SiO5 kyanite (~91.4 vol%) and trigonal Al2 O3 corundum (~8.6 vol%) fabricated at high pressure (10 GPa) and temperature (1200‐1400°C) were investigated. It is already known that the optical transparency of kyanite‐based nanoceramics increases with decreasing average grain size. The present study shows that the hardness of these ceramics increases with decreasing grain sizes down to ~70 nm according to the Hall‐Petch strengthening. This grain size seems to mark a transition range where an inverse Hall‐Petch effect is indicated due to signs of a moderate hardness decrease at a smaller grain size of ~35 nm. The observed hardness‐grain size relation can fairly be described by an existing composite model, which considers the crystals to be harder than the noncrystalline grain boundaries. Within the range of average grain sizes examined, the kyanite habit changes from more equant to more columnar. This behavior is associated with the observed strong crack deflection by the columnar kyanite grains with aspect (length to diameter) ratios ranging from ~2 to 10 and may positively affect the fracture toughness. Abstract : Transparent nanoceramics, synthesized at extreme conditions of high pressure and temperature, are new classes of materials highly attractive for photonic applications, such as optical windows, which require additional increased hardness and toughness. In this study, mechanical properties of transparent polycrystalline nanoceramics consisting of triclinic Al2 SiO5 kyanite (~91.4 vol%) and trigonal Al2 O3 corundum (~8.6 vol%) fabricated at high pressure (10 GPa) and temperature (1200‐1400°C) were investigated. Together with the optical transparency, the Vickers hardness increases with decreasing grain sizes down to 50‐70 nm following the Hall‐Petch strengthening. These data allow to draw comparison of theoretical predictions with experimental data and, thus, to advance the knowledge on the influence of nanostructures, including intercrystalline components, on material reinforcement.